Old Ideals and New Realities: The Changing Context of Adolescent Partnerships in Cebu, Philippines - Gipson, Jessica D. (2012)
The Philippines has experienced rapid sociodemographic changes in recent years, with implications for adolescents. This study combines quantitative and qualitative data from Metro Cebu to assess the timing and predictors of adolescent partnerships, as well as the context in which these partnerships are occurring. The majority of adolescents (54%) had premarital sex, though this pattern varied by gender. Wealthier, urban men, and women with less education and lower reported religiosity, were more likely to have premarital sex. Engagement in risk behaviors was predictive of premarital sex for both males and females. The qualitative data contextualize the circumstances under which adolescents engage in sex and form partnerships, and illustrate how sociocultural norms contribute to gender differences in partnership patterns. Given the ‘new’ realities of young Filipinos’ lives, targeted efforts to support adolescents’ transition to adulthood are needed to avert potentially adverse lifeevents.